Needs to develop and expose communities’ knowledge: Inaugural editorial statement - Kananga Robert Mukuna; Mokgadi Moletsane; Fumane Portia Khanare; Liu Woon Chia; Tlale Lloyd; Peter Aloka; Charity Okeke; Thomas Mabasa; Ifeoma Eze; Christa Beyers (International Journal of Studies in Psychology)
Dear authors and reviewers, We celebrated the first issue of the International Journal of Studies in Psychology (IJSPSY). We are excited and inspired to start this new journey through its mission and objective. We believed that IJSPSY is a reality responding to ensure that our knowledge is continuously relevant and responsive to different communities' needs. The understanding of diversity in psychology could bring various cultures together. The genesis of the world revealed that human beings are born with inherent abilities, talents, and capacities; and build on the strengths and talents they already have to improve their holistic well-being. We do not always have to reinvent ourselves for successful well-being. Instead, we need to find ways to deploy “best self” in new and significant ways, bringing knowledge systems in psychology, augmenting, enabling, and enhancing holistic learning with the vision of the International Journal of Studies in Psychology (IJSPSY). This should be done by conducting responsive research and has significant relevance to the researchers, scholars, practitioners, and policymakers that the IJSPSY Editorial Board voted to launch a new journal. The IJSPSY's goal is to shape psychology studies' direction by encouraging scholarship that affects research and practice in public and private sectors, solving complex, interconnected, and interrelated problems. Furthermore, it helps to connect with other disciplines and produce ‘quantum’ knowledge, rather than fragmented and binary knowledge systems.